Trends in amorphous solid dispersion drug products approved by the U.S. Food and Drug Administration between 2012 and 2023 - Moseson, Dana E.; Tran, Trong Bien; Karunakaran, Bharathi; Ambardekar, Rohan; Hiew, Tze Ning (International journal of pharmaceutics: X, 2024)
Forty-eight (48) drug products (DPs) containing amorphous solid dispersions (ASDs) have been approved by the U.S. Food and Drug Administration in the 12-year period between 2012 and 2023. These DPs comprise 36 unique amorphous drugs. Ten (10) therapeutic categories are represented, with most DPs containing antiviral and antineoplastic agents. The most common ASD polymers are copovidone (49%) and hypromellose acetate succinate (30%), while spray drying (54%) and hot melt extrusion (35%) are the most utilized manufacturing processes to prepare the ASD drug product intermediate (DPI). Tablet dosage forms are the most common, with several capsule products available. Line extensions of several DPs based on flexible oral solids and powders for oral suspension have been approved which provide patient-centric dosing to pediatric and other patient populations. The trends in the use of common excipients and film coating types are discussed. Eighteen (18) DPs are fixed-dose combinations, and some contain a mixture of amorphous and crystalline drugs. The DPs have dose/unit of amorphous drug ranging from <5 mg up to 300 mg, with the majority being ≤100 mg/unit. This review details several aspects of DPI and DP formulation and manufacturing of ASDs, as well as trends related to therapeutic category, dose, and patient-centricity. [Display omitted]